Degradable double-sided leather and preparation method thereof
By using polylactic acid or PHBV fiber cloth as the substrate in the degradable artificial leather materials, combining silicone coating and surface treatment layer, and using modified silicone and nanofiller components, the existing materials have been solved to solve the problem of taking into account the performance and degradability, and high-performance and environmentally friendly degradable double-sided leather materials are achieved.
Patent Information
- Application Number
- CN202411767947.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
AI Technical Summary
Existing degradable artificial leather materials are difficult to balance between performance and degradability, and the use of organic solvents in traditional preparation processes leads to environmental pollution and safety risks.
Polylactic acid (PLA) or PHBV fiber cloth is used as the substrate, combined with the silicone coating and surface treatment layer, and the polycaprolactone modified polydimethylsiloxane and polylactic acid grafted polysiloxane are designed and synthesized, nanosilica, cellulose nanocrystals and degradable starch-based toughening agent are added, and solvent-free preparation process is adopted.
It achieves excellent degradability, excellent mechanical properties, excellent comfort and good weather resistance of the material, while avoiding the use of organic solvents, reducing environmental impact and harmful substance residues in the product.
Smart Images

Figure BDA0005169474320000231 
Figure BDA0005169474320000232 
Figure BDA0005169474320000241
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of degradable materials, in particular to degradable double-face leather and a preparation method thereof. Background Art
[0002] With the continuous improvement of environmental protection awareness, the application of degradable materials in various fields is becoming more and more extensive. In the field of leather substitutes, the development of degradable double-sided leather with excellent performance and environmental friendliness has become an important research direction. There have been some reports on degradable artificial leather in the prior art, which mainly use bio-based polymers such as polylactic acid (PLA), polyhydroxyalkanoate (PHA), etc. as substrates, and prepare artificial leather materials with certain degradability through blending, compounding and other methods. However, these materials are often difficult to balance between performance and degradability. Either the degradability is insufficient or the mechanical properties are poor, which cannot meet the needs of practical applications.
[0003] In addition, the traditional artificial leather preparation process usually involves the use of organic solvents, which not only causes environmental pollution, but may also remain in the product and affect its safety. At the same time, the existing biodegradable artificial leather also has obvious deficiencies in terms of comfort and weather resistance, making it difficult to compete with natural leather in high-end application areas.
[0004] Therefore, there is an urgent need to develop a new type of degradable double-faced leather material and a preparation method thereof to solve the problems existing in the prior art. Summary of the invention
[0005] The present invention aims to provide a double-face leather material having excellent degradability, outstanding mechanical properties, good comfort and outstanding weather resistance, while adopting an environmentally friendly preparation process to meet the growing demand for sustainable development.
[0006] The object of the present invention is to provide a degradable double-face leather, comprising the following components by weight:
[0007] (1) Substrate, selected from one or more of the following:
[0008] a) Surface density is 50-150g / m 2 Polylactic acid PLA non-woven fabric;
[0009] b) Surface density is 60-180g / m 2 PHBV fiber cloth;
[0010] c) a polycaprolactone PCL film having a thickness of 20-80 μm;
[0011] (2) Silicone coating, including:
[0012] a) 40-60 parts by weight of polydimethylmethylvinylsiloxane;
[0013] b) 20-40 parts by weight of polycaprolactone modified polydimethylsiloxane;
[0014] c) 10-30 parts by weight of polylactic acid grafted polysiloxane;
[0015] d) 2-5 parts by weight of vinyltrimethoxysilane;
[0016] e) 0.5-2 parts by weight of a platinum catalyst;
[0017] f) 3-8 parts by weight of nano silicon dioxide;
[0018] g) 1-5 parts by weight of a degradable starch-based toughening agent;
[0019] h) 0.1-0.5 parts by weight of trimethyloctadecylammonium chloride;
[0020] i) 0.5-2 parts by weight of cellulose nanocrystals;
[0021] j) 0.5-2 parts by weight of a natural vegetable oil-based matting agent;
[0022] k) 0.1-0.5 parts by weight of a bio-based dispersant;
[0023] (3) Surface treatment layer, including:
[0024] a) 40-60 parts by weight of polyethylene glycol dimethyl siloxane copolymer;
[0025] b) 5-15 parts by weight of hydrolyzed silk protein;
[0026] c) 10-30 parts by weight of triethyl citrate;
[0027] d) 1-5 parts by weight of nanocellulose.
[0028] Preferably, the PCL content of the polycaprolactone-modified polydimethylsiloxane is 10-30 wt % and the molecular weight is 15,000-40,000 g / mol.
[0029] Preferably, the PLA content of the polylactic acid grafted polysiloxane is 5-15 wt % and the molecular weight is 10,000-30,000 g / mol.
[0030] Preferably, the maleic anhydride grafting degree of the degradable starch-based toughening agent is 5-15%, and the water content is ≤5%.
[0031] Preferably, the polyethylene glycol dimethyl siloxane copolymer has a PEG content of 20-40 wt % and a molecular weight of 15,000-50,000 g / mol.
[0032] A method for producing degradable double-face leather, comprising the following steps:
[0033] (1) Substrate pretreatment:
[0034] a) cutting the selected degradable substrate into required sizes;
[0035] b) using a plasma treatment device to activate the surface of the substrate, wherein the gas pressure is 50-100 Pa, the radio frequency power is 50-200 W, and the treatment time is 30-120 seconds;
[0036] c) storing the treated substrate in a dust-free environment with a relative humidity of 40-60% and a temperature of 20-25° C.;
[0037] (2) Preparation of silicone coating:
[0038] a) adding polydimethylmethylvinylsiloxane, polycaprolactone-modified polydimethylsiloxane and polylactic acid-grafted polysiloxane in a reaction kettle in order according to the formula ratio, and stirring at 25-30° C. at a speed of 300-500 rpm for 15-30 minutes;
[0039] b) Slowly add nano-silicon dioxide and continue stirring for 30-60 minutes;
[0040] c) adding a degradable starch-based toughening agent, trimethyl octadecyl ammonium chloride, cellulose nanocrystals, a natural vegetable oil-based matting agent, and a bio-based dispersant in sequence, stirring for 10-15 minutes after each addition of a component;
[0041] d) finally adding vinyltrimethoxysilane and stirring for 5-10 minutes;
[0042] (3) Coating application:
[0043] a) transferring the premix into the hopper of the coater;
[0044] b) using a release paper with a texture as a carrier, the mixture is evenly coated on the release paper by a comma knife, the coating speed is 5-10 m / min, and the coating thickness is 20-30 μm;
[0045] c) passing the release paper coated with the mixture through a preheating zone at a temperature of 60-70° C. for 60-90 seconds;
[0046] d) at the exit of the preheating zone, covering the pretreated substrate on the semi-cured silicone layer;
[0047] e) Using a pressure roller to press the substrate onto the silicone layer, the roller pressure is 50-100 N / cm;
[0048] f) passing the laminated composite material through a main drying zone at a temperature of 120-140° C. for 2-4 minutes;
[0049] g) cooling to room temperature, and then peeling off the release paper;
[0050] (4) Double-sided coating: Repeat steps (2) and (3) to coat the other side of the material;
[0051] (5) Surface treatment:
[0052] a) adding polyethylene glycol dimethylsiloxane copolymer into a stirred tank, stirring at 300 rpm, and heating to 60° C.;
[0053] b) slowly adding hydrolyzed silk protein and continuing stirring for 30 minutes;
[0054] c) adding triethyl citrate and stirring for 15 minutes;
[0055] d) finally adding nanocellulose, increasing the stirring speed to 500 rpm, and stirring for 60 minutes;
[0056] e) Cool to room temperature and let stand for 24 hours;
[0057] f) Use a 120 mesh treatment roller to evenly apply the surface treatment agent on both sides of the double-sided silicone coating material, with a coating weight of 10-20g / m 2 (per side), coating speed is 3-5m / min;
[0058] g) passing the coated material through a drying zone at a temperature of 100-120°C for 2-3 minutes;
[0059] h) Cool to room temperature and roll up for storage.
[0060] Preferably, the preparation method of the polycaprolactone-modified polydimethylsiloxane comprises:
[0061] a) Add 100 g of polydimethylsiloxane (molecular weight 5000-10000 g / mol) into a three-necked round-bottom flask;
[0062] b) adding 10-30 g of ε-caprolactone monomer and 0.5-1.5 g of stannate catalyst;
[0063] c) Under nitrogen protection, heat to 130-150°C and stir to react for 4-6 hours;
[0064] d) Cool to room temperature, precipitate the product with ethanol, filter, and vacuum dry to obtain the final product.
[0065] Preferably, the preparation method of the polylactic acid grafted polysiloxane comprises:
[0066] a) adding 200 g of hydroxyl-terminated polydimethylsiloxane (molecular weight 3000-8000 g / mol) into a three-necked round-bottom flask;
[0067] b) adding 10-30 g L-lactic acid and 0.5-1.0 g p-toluenesulfonic acid as catalysts;
[0068] c) at 130-150° C., reducing the pressure to 20-50 mbar, stirring and reacting for 6-8 hours;
[0069] d) Cool to room temperature, precipitate the product with acetone, filter, and vacuum dry to obtain the final product.
[0070] Preferably, the preparation method of the degradable starch-based toughening agent comprises:
[0071] a) Add 200 g corn starch and 600 mL deionized water into a reactor;
[0072] b) adding 20-40 g of glycerol as a plasticizer;
[0073] c) stirring at 90-95° C. for 1-2 hours for gelatinization;
[0074] d) Cool to 60°C, add 10-20g of maleic anhydride, and continue the reaction for 1 hour;
[0075] e) cooling the product, centrifuging and freeze-drying to obtain the final product.
[0076] Preferably, the preparation method of the polyethylene glycol dimethylsiloxane copolymer comprises:
[0077] a) adding 200 g of α-hydrogen-ω-hydroxy-polydimethylsiloxane (molecular weight 5000-10000 g / mol) into a three-necked round-bottom flask;
[0078] b) adding 50-100 g of methoxy polyethylene glycol (PEG molecular weight 1000-5000 Da);
[0079] c) adding 1-2 g of platinum catalyst;
[0080] d) stirring and reacting at 80-100° C. under nitrogen protection for 4-6 hours;
[0081] e) cooling to room temperature, precipitating the product with n-hexane, filtering, and vacuum drying to obtain the final product.
[0082] The innovations of the present invention are mainly reflected in the following aspects:
[0083] First, the present invention cleverly combines organosilicon chemistry with biodegradable materials. By designing and synthesizing polycaprolactone-modified polydimethylsiloxane and polylactic acid-grafted polysiloxane, easily degradable ester bonds are introduced while maintaining the excellent properties of silica gel. This molecular design makes full use of the flexibility and stability of the organosilicon skeleton, while achieving controllable degradation through the introduction of ester bonds. From the perspective of molecular orbital theory, the σ bond and π bond contributions of the silicon-oxygen bond give the main chain excellent flexibility, while the polarity and spatial configuration of the ester group are conducive to the attachment of microorganisms and the action of enzymes, thereby promoting the biodegradation process of the material.
[0084] Secondly, the present invention adopts a synergistic reinforcement strategy of multiple nanofillers and bio-based toughening agents. Nano-silicon dioxide, through its unique surface chemical properties, can form a strong interaction with the siloxane network, significantly improving the mechanical strength of the material. Cellulose nanocrystals use their high aspect ratio and excellent mechanical properties to form an interconnected network structure in the material, greatly improving the toughness of the material. The degradable starch-based toughening agent not only improves the flexibility of the material, but also increases the hygroscopicity and biocompatibility of the material through its hydrophilic functional groups. The synergistic effect between these components forms a multi-scale, multifunctional composite reinforcement system, achieving a comprehensive improvement in material performance.
[0085] Thirdly, the present invention innovatively introduces hydrolyzed silk protein and triethyl citrate into the surface treatment layer. The rich amino acid composition of hydrolyzed silk protein not only provides excellent hygroscopicity and skin-friendliness, but its special secondary structure may also form a microscopic "capillary" network on the surface of the material, greatly improving the air permeability of the material. As a new type of bio-based plasticizer, triethyl citrate not only increases the softness of the material, but the conjugated system in its molecular structure may also play the role of a UV absorber, significantly improving the weather resistance of the material.
[0086] Finally, the present invention adopts an innovative solvent-free preparation process. Through the carefully designed preheating, pressing and drying process, the effective combination of the components and the formation of the network are achieved, while avoiding the use of organic solvents. This not only reduces the environmental impact of the production process, but also reduces the residual harmful substances in the product, and improves the safety and environmental friendliness of the product.
[0087] The beneficial effects of the present invention are mainly reflected in the following aspects:
[0088] 1. Excellent degradability: Through molecular design and multi-component synergy, rapid and complete biodegradation is achieved, with a weight loss rate of more than 95% within 180 days, far exceeding traditional degradable materials.
[0089] 2. Excellent mechanical properties: The synergistic effect of various nanofillers and toughening agents gives the material excellent tensile strength, elongation at break and folding resistance, which fully meets the needs of practical applications.
[0090] 3. Excellent comfort: Hydrolyzed silk protein and special microstructure design give the material excellent air permeability and moisture absorption, with a feel score of 4.8 points (out of 5 points).
[0091] 4. Good weather resistance: The innovative surface treatment solution enables the material to maintain more than 95% of its mechanical properties after 1000 hours of accelerated aging, with a color difference of less than 2.5.
[0092] 5. Environmental friendliness: Solvent-free process and the use of bio-based raw materials make the product have extremely low VOC emission (<0.15mg / m 2 ·h) and heavy metal content (<1mg / kg).
[0093] 6. Versatility: By adjusting the formula and process parameters, it can flexibly meet the needs of different application scenarios, such as clothing, luggage, furniture and other fields.
[0094] In summary, the present invention has successfully developed a new type of biodegradable double-sided leather material with both high performance and environmental friendliness through innovative molecular design, multi-component synergy and green preparation process, providing an effective solution to the environmental problems and performance challenges faced by the traditional artificial leather industry, and has important theoretical significance and application value. DETAILED DESCRIPTION
[0095] Example 1
[0096] This embodiment provides a degradable double-sided leather and a preparation method thereof. The degradable double-sided leather comprises the following components:
[0097] The surface density of the substrate is 50g / m 2 The polylactic acid (PLA) nonwoven fabric is made of 40 parts by weight of polydimethylmethylvinylsiloxane, 20 parts by weight of polycaprolactone modified polydimethylsiloxane, 10 parts by weight of polylactic acid grafted polysiloxane, 2 parts by weight of vinyltrimethoxysilane, 0.5 parts by weight of platinum catalyst, 3 parts by weight of nano-silicon dioxide, 1 part by weight of degradable starch-based toughening agent, 0.1 parts by weight of trimethyloctadecyl ammonium chloride, 0.5 parts by weight of cellulose nanocrystals, 0.5 parts by weight of natural plant oil-based matting agent and 0.1 parts by weight of bio-based dispersant. The surface treatment layer contains 40 parts by weight of polyethylene glycol dimethylsiloxane copolymer, 5 parts by weight of hydrolyzed silk protein, 10 parts by weight of triethyl citrate and 1 part by weight of nano-cellulose.
[0098] The preparation method of the degradable double-faced leather comprises the following steps:
[0099] First, pre-treat the substrate. 2 The polylactic acid (PLA) non-woven fabric is cut into the required size, and then the surface of the substrate is activated using a plasma treatment device. The treatment parameters are: air pressure 50Pa, RF power 50W, and treatment time 30 seconds. The treated substrate is stored in a dust-free environment with a relative humidity of 40% and a temperature of 20°C.
[0100] Secondly, prepare the silica gel coating. Add 40 parts by weight of polydimethylmethylvinylsiloxane (molecular weight 10,000Da, vinyl content 0.5mol%), 20 parts by weight of polycaprolactone modified polydimethylsiloxane (PCL content 10wt%, molecular weight 15,000g / mol) and 10 parts by weight of polylactic acid grafted polysiloxane (PLA content 5wt%, molecular weight 10,000g / mol) into the reaction kettle in sequence. Stir at 300rpm for 15 minutes at 25°C. Then slowly add 3 parts by weight of nano-silicon dioxide (average particle size 10nm) and continue stirring for 30 minutes. 1 part by weight of a degradable starch-based toughener (maleic anhydride grafting degree 5%, moisture content 5%), 0.1 part by weight of trimethyl octadecyl ammonium chloride, 0.5 part by weight of cellulose nanocrystals (length 100 nm, diameter 5 nm), 0.5 part by weight of a natural vegetable oil-based matting agent (acid value 50 mg KOH / g) and 0.1 part by weight of a bio-based dispersant were added in sequence, and stirred for 10 minutes after each addition of a component. Finally, 2 parts by weight of vinyl trimethoxy silane were added and stirred for 5 minutes.
[0101] Next, the coating application is carried out. The premix is transferred to the hopper of the coater and the mixture is evenly coated on the release paper using a textured release paper as a carrier by a comma knife. The coating speed is 5m / min and the coating thickness is 20μm. The release paper coated with the mixture is passed through the preheating zone at a temperature of 60°C for 60 seconds. At the exit of the preheating zone, the pretreated substrate is covered with the semi-cured silicone layer. The substrate is pressed onto the silicone layer using a pressure roller with a roller pressure of 50N / cm. The pressed composite material is passed through the main drying zone at a temperature of 120°C for 2 minutes. After cooling to room temperature, the release paper is peeled off.
[0102] Then, the above coating steps are repeated to perform coating treatment on the other side of the material to obtain a double-sided coating material.
[0103] Finally, perform surface treatment. Add 40 parts by weight of polyethylene glycol dimethylsiloxane copolymer (PEG content 20wt%, molecular weight 15,000g / mol) to the stirring kettle, stir at 300rpm, and heat to 60°C. Slowly add 5 parts by weight of hydrolyzed silk protein (molecular weight 5000Da) and continue stirring for 30 minutes. Add 10 parts by weight of triethyl citrate and stir for 15 minutes. Finally, add 1 part by weight of nanocellulose (diameter 4nm, length 100nm), increase the stirring speed to 500rpm, and stir for 60 minutes. Cool to room temperature and let stand for 24 hours. Use a 120-mesh treatment roller to evenly apply the surface treatment agent on both sides of the double-sided silicone coating material, with a coating weight of 10g / m 2 (per side), the coating speed is 3m / min. The coated material is passed through a drying zone at a temperature of 100°C for 2 minutes. After cooling to room temperature, it is rolled up and stored to obtain the final degradable double-sided leather product.
[0104] In this embodiment, the preparation method of polycaprolactone modified polydimethylsiloxane is as follows: 100g of polydimethylsiloxane (molecular weight 5000g / mol) is added to a 250mL three-necked round-bottom flask. 10g of ε-caprolactone monomer and 0.5g of dibutyltin dilaurate catalyst are added. Under nitrogen protection, the temperature is raised to 130°C and stirred for reaction for 4 hours. Cool to room temperature, precipitate the product with ethanol, filter, and vacuum dry to obtain the final product.
[0105] The preparation method of polylactic acid grafted polysiloxane is as follows: 200g of hydroxyl-terminated polydimethylsiloxane (molecular weight 3000g / mol) is added to a 500mL three-necked round-bottom flask. 10g of L-lactic acid and 0.5g of p-toluenesulfonic acid are added as catalysts. At 130°C, the pressure is reduced to 20mbar and stirred for reaction for 6 hours. Cool to room temperature, precipitate the product with acetone, filter, and vacuum dry to obtain the final product.
[0106] The preparation method of the degradable starch-based toughening agent is as follows: 200 g corn starch and 600 mL deionized water are added to a 1000 mL reactor. 20 g glycerol is added as a plasticizer. The mixture is stirred at 90° C. for 1 hour for gelatinization. The mixture is cooled to 60° C., 10 g maleic anhydride is added, and the reaction is continued for 1 hour. The product is cooled, centrifuged, and freeze-dried to obtain the final product.
[0107] The preparation method of polyethylene glycol dimethylsiloxane copolymer is as follows: 200g α-hydrogen-ω-hydroxy-polydimethylsiloxane (molecular weight 5000g / mol) is added to a 500mL three-necked round-bottom flask. 50g methoxy polyethylene glycol (PEG molecular weight 1000Da) is added. 1g platinum catalyst (Castells catalyst) is added. The mixture is stirred and reacted for 4 hours at 80°C under nitrogen protection. The mixture is cooled to room temperature, the product is precipitated with n-hexane, filtered, and vacuum dried to obtain the final product.
[0108] The degradable double-sided leather in this embodiment has excellent degradability and mechanical strength. The polylactic acid (PLA) non-woven fabric substrate provides the product with good air permeability and softness, while ensuring the degradability of the product. The polycaprolactone-modified polydimethylsiloxane and polylactic acid-grafted polysiloxane in the silicone coating not only improve the degradability of the product, but also enhance the compatibility between the silicone coating and the substrate. The addition of nano-silicon dioxide improves the mechanical strength and wear resistance of the coating. The degradable starch-based toughening agent improves the flexibility of the product without affecting its degradability. Trimethyloctadecyl ammonium chloride, as an antistatic agent, effectively reduces the static electricity accumulation of the product during use. The addition of cellulose nanocrystals further enhances the mechanical properties and barrier properties of the coating. The natural plant oil-based matting agent not only adjusts the glossiness of the product surface, but also improves the biocompatibility of the product. The hydrolyzed silk protein and triethyl citrate in the surface treatment layer give the product excellent feel and skin-friendliness while maintaining good degradability.
[0109] Example 2
[0110] This embodiment provides another degradable double-sided leather and a preparation method thereof. The degradable double-sided leather comprises the following components:
[0111] The surface density of the substrate is 120g / m 2 The polyhydroxybutyric acid-hydroxyvaleric acid copolymer (PHBV) fiber cloth. The silica gel coating is composed of 50 parts by weight of polydimethylmethylvinylsiloxane, 30 parts by weight of polycaprolactone modified polydimethylsiloxane, 20 parts by weight of polylactic acid grafted polysiloxane, 3.5 parts by weight of vinyltrimethoxysilane, 1.25 parts by weight of platinum catalyst, 5.5 parts by weight of nano-silicon dioxide, 3 parts by weight of degradable starch-based toughening agent, 0.3 parts by weight of trimethyloctadecyl ammonium chloride, 1.25 parts by weight of cellulose nanocrystals, 1.25 parts by weight of natural plant oil-based matting agent and 0.3 parts by weight of bio-based dispersant. The surface treatment layer contains 50 parts by weight of polyethylene glycol dimethylsiloxane copolymer, 10 parts by weight of hydrolyzed silk protein, 20 parts by weight of triethyl citrate and 3 parts by weight of nanocellulose.
[0112] The preparation method of the degradable double-faced leather comprises the following steps:
[0113] First, pre-treat the substrate. 2 The polyhydroxybutyric acid-hydroxyvaleric acid copolymer (PHBV) fiber cloth was cut into the required size, and then the surface of the substrate was activated using a plasma treatment device. The treatment parameters were: air pressure 75Pa, radio frequency power 125W, and treatment time 75 seconds. The treated substrate was stored in a dust-free environment with a relative humidity of 50% and a temperature of 22.5°C.
[0114] Secondly, prepare the silica gel coating. Add 50 parts by weight of polydimethylmethylvinylsiloxane (molecular weight 30,000Da, vinyl content 1.25mol%), 30 parts by weight of polycaprolactone modified polydimethylsiloxane (PCL content 20wt%, molecular weight 27,500g / mol) and 20 parts by weight of polylactic acid grafted polysiloxane (PLA content 10wt%, molecular weight 20,000g / mol) into the reaction kettle in sequence. Stir at 400rpm for 22.5 minutes at 27.5°C. Then slowly add 5.5 parts by weight of nano-silicon dioxide (average particle size 30nm) and continue stirring for 45 minutes. 3 parts by weight of a degradable starch-based toughener (maleic anhydride grafting degree 10%, moisture content 4%), 0.3 parts by weight of trimethyl octadecyl ammonium chloride, 1.25 parts by weight of cellulose nanocrystals (length 300nm, diameter 12.5nm), 1.25 parts by weight of a natural vegetable oil-based matting agent (acid value 65mg KOH / g) and 0.3 parts by weight of a bio-based dispersant were added in sequence, and stirred for 12.5 minutes after each component was added. Finally, 3.5 parts by weight of vinyl trimethoxy silane was added and stirred for 7.5 minutes.
[0115] Next, the coating is applied. The premix is transferred to the hopper of the coater and the mixture is evenly coated on the release paper using a textured release paper as a carrier by a comma knife. The coating speed is 7.5m / min and the coating thickness is 25μm. The release paper coated with the mixture is passed through the preheating zone at a temperature of 65°C for 75 seconds. At the exit of the preheating zone, the pretreated substrate is covered with the semi-cured silicone layer. The substrate is pressed onto the silicone layer using a pressure roller with a roller pressure of 75N / cm. The pressed composite material is passed through the main drying zone at a temperature of 130°C for 3 minutes. After cooling to room temperature, the release paper is peeled off.
[0116] Then, the above coating steps are repeated to perform coating treatment on the other side of the material to obtain a double-sided coating material.
[0117] Finally, perform surface treatment. Add 50 parts by weight of polyethylene glycol dimethylsiloxane copolymer (PEG content 30wt%, molecular weight 32,500g / mol) to the stirring kettle, stir at 300rpm, and heat to 60°C. Slowly add 10 parts by weight of hydrolyzed silk protein (molecular weight 10,000Da) and continue stirring for 30 minutes. Add 20 parts by weight of triethyl citrate and stir for 15 minutes. Finally, add 3 parts by weight of nanocellulose (diameter 7nm, length 300nm), increase the stirring speed to 500rpm, and stir for 60 minutes. Cool to room temperature and let stand for 24 hours. Use a 120-mesh treatment roller to evenly apply the surface treatment agent on both sides of the double-sided silicone coating material, with a coating weight of 15g / m 2 (per side), the coating speed is 4m / min. The coated material is passed through a drying zone at a temperature of 110°C for 2.5 minutes. After cooling to room temperature, it is rolled up and stored to obtain the final degradable double-sided leather product.
[0118] In this embodiment, the preparation method of polycaprolactone modified polydimethylsiloxane is as follows: 100g of polydimethylsiloxane (molecular weight 7500g / mol) is added to a 250mL three-necked round-bottom flask. 20g of ε-caprolactone monomer and 1g of dibutyltin dilaurate catalyst are added. Under nitrogen protection, the temperature is raised to 140°C and stirred for reaction for 5 hours. Cool to room temperature, precipitate the product with ethanol, filter, and vacuum dry to obtain the final product.
[0119] The preparation method of polylactic acid grafted polysiloxane is as follows: 200g of hydroxyl-terminated polydimethylsiloxane (molecular weight 5500g / mol) is added to a 500mL three-necked round-bottom flask. 20g of L-lactic acid and 0.75g of p-toluenesulfonic acid are added as catalysts. At 140°C, the pressure is reduced to 35mbar and stirred for reaction for 7 hours. Cool to room temperature, precipitate the product with acetone, filter, and vacuum dry to obtain the final product.
[0120] The preparation method of the degradable starch-based toughening agent is as follows: 200 g corn starch and 600 mL deionized water are added to a 1000 mL reactor. 30 g glycerol is added as a plasticizer. The mixture is stirred at 92.5° C. for 1.5 hours for gelatinization. The mixture is cooled to 60° C., 15 g maleic anhydride is added, and the reaction is continued for 1 hour. The product is cooled, centrifuged, and freeze-dried to obtain the final product.
[0121] The preparation method of polyethylene glycol dimethylsiloxane copolymer is as follows: 200g α-hydrogen-ω-hydroxy-polydimethylsiloxane (molecular weight 7500g / mol) is added to a 500mL three-necked round-bottom flask. 75g methoxy polyethylene glycol (PEG molecular weight 3000Da) is added. 1.5g platinum catalyst (Castells catalyst) is added. The mixture is stirred and reacted for 5 hours at 90°C under nitrogen protection. The mixture is cooled to room temperature, the product is precipitated with n-hexane, filtered, and vacuum dried to obtain the final product.
[0122] The degradable double-sided leather in this embodiment further improves the mechanical strength and durability of the product while maintaining good degradability. The polyhydroxybutyric acid-hydroxyvaleric acid copolymer (PHBV) fiber cloth substrate not only has excellent degradability, but also provides higher strength and toughness. The increase in the content of polycaprolactone-modified polydimethylsiloxane and polylactic acid-grafted polysiloxane in the silicone coating further enhances the degradability of the coating and its compatibility with the substrate. Higher contents of nano-silicon dioxide and cellulose nanocrystals significantly improve the mechanical strength, wear resistance and barrier properties of the coating. The increased content of degradable starch-based toughening agent improves the flexibility and folding resistance of the product. The increase in the content of hydrolyzed silk protein and triethyl citrate in the surface treatment layer makes the product softer to the touch and better skin-friendly.
[0123] Example 3
[0124] This embodiment provides a third degradable double-sided leather and a preparation method thereof. The degradable double-sided leather comprises the following components:
[0125] The substrate is a polycaprolactone (PCL) film with a thickness of 50 μm. The silicone coating is composed of 60 parts by weight of polydimethylmethylvinylsiloxane, 40 parts by weight of polycaprolactone-modified polydimethylsiloxane, 30 parts by weight of polylactic acid grafted polysiloxane, 5 parts by weight of vinyltrimethoxysilane, 2 parts by weight of platinum catalyst, 8 parts by weight of nano-silicon dioxide, 5 parts by weight of degradable starch-based toughening agent, 0.5 parts by weight of trimethyloctadecyl ammonium chloride, 2 parts by weight of cellulose nanocrystals, 2 parts by weight of natural plant oil-based matting agent and 0.5 parts by weight of bio-based dispersant. The surface treatment layer contains 60 parts by weight of polyethylene glycol dimethylsiloxane copolymer, 15 parts by weight of hydrolyzed silk protein, 30 parts by weight of triethyl citrate and 5 parts by weight of nanocellulose.
[0126] The preparation method of the degradable double-faced leather comprises the following steps:
[0127] First, the substrate was pretreated. A 50 μm thick polycaprolactone (PCL) film was cut into the required size, and then the surface of the substrate was activated using a plasma treatment device. The treatment parameters were: air pressure 100 Pa, RF power 200 W, and treatment time 120 seconds. The treated substrate was stored in a dust-free environment with a relative humidity of 60% and a temperature of 25°C.
[0128] Secondly, prepare the silica gel coating. Add 60 parts by weight of polydimethylmethylvinylsiloxane (molecular weight 50,000Da, vinyl content 2.0mol%), 40 parts by weight of polycaprolactone modified polydimethylsiloxane (PCL content 30wt%, molecular weight 40,000g / mol) and 30 parts by weight of polylactic acid grafted polysiloxane (PLA content 15wt%, molecular weight 30,000g / mol) into the reaction kettle in sequence. Stir at 500rpm for 30 minutes at 30°C. Then slowly add 8 parts by weight of nano-silicon dioxide (average particle size 50nm) and continue stirring for 60 minutes. 5 parts by weight of a degradable starch-based toughener (maleic anhydride grafting degree 15%, moisture content 3%), 0.5 parts by weight of trimethyl octadecyl ammonium chloride, 2 parts by weight of cellulose nanocrystals (length 500nm, diameter 20nm), 2 parts by weight of a natural vegetable oil-based matting agent (acid value 80mgKOH / g) and 0.5 parts by weight of a bio-based dispersant were added in sequence, and stirred for 15 minutes after each component was added. Finally, 5 parts by weight of vinyl trimethoxy silane was added and stirred for 10 minutes.
[0129] Next, the coating application is carried out. The premix is transferred to the hopper of the coater and the mixture is evenly coated on the release paper using a textured release paper as a carrier by a comma knife. The coating speed is 10m / min and the coating thickness is 30μm. The release paper coated with the mixture is passed through the preheating zone at a temperature of 70°C for 90 seconds. At the exit of the preheating zone, the pretreated substrate is covered with the semi-cured silicone layer. The substrate is pressed onto the silicone layer using a pressure roller with a roller pressure of 100N / cm. The pressed composite material is passed through the main drying zone at a temperature of 140°C for 4 minutes. After cooling to room temperature, the release paper is peeled off.
[0130] Then, the above coating steps are repeated to perform coating treatment on the other side of the material to obtain a double-sided coating material.
[0131] Finally, perform surface treatment. Add 60 parts by weight of polyethylene glycol dimethylsiloxane copolymer (PEG content 40wt%, molecular weight 50,000g / mol) to the stirring kettle, stir at 300rpm, and heat to 60°C. Slowly add 15 parts by weight of hydrolyzed silk protein (molecular weight 15,000Da) and continue stirring for 30 minutes. Add 30 parts by weight of triethyl citrate and stir for 15 minutes. Finally, add 5 parts by weight of nanocellulose (diameter 10nm, length 500nm), increase the stirring speed to 500rpm, and stir for 60 minutes. Cool to room temperature and let stand for 24 hours. Use a 120-mesh treatment roller to evenly apply the surface treatment agent on both sides of the double-sided silicone coating material, with a coating weight of 20g / m 2 (per side), the coating speed is 5m / min. The coated material is passed through a drying zone at a temperature of 120°C for 3 minutes. After cooling to room temperature, it is rolled up and stored to obtain the final degradable double-sided leather product.
[0132] In this embodiment, the preparation method of polycaprolactone modified polydimethylsiloxane is as follows: 100g polydimethylsiloxane (molecular weight 10000g / mol) is added to a 250mL three-necked round-bottom flask. 30g ε-caprolactone monomer and 1.5g dibutyltin dilaurate catalyst are added. Under nitrogen protection, the temperature is raised to 150°C and the reaction is stirred for 6 hours. Cool to room temperature, precipitate the product with ethanol, filter, and vacuum dry to obtain the final product.
[0133] The preparation method of polylactic acid grafted polysiloxane is as follows: 200g of hydroxyl-terminated polydimethylsiloxane (molecular weight 8000g / mol) is added to a 500mL three-necked round-bottom flask. 30g of L-lactic acid and 1.0g of p-toluenesulfonic acid are added as catalysts. At 150°C, the pressure is reduced to 50mbar and stirred for reaction for 8 hours. Cool to room temperature, precipitate the product with acetone, filter, and vacuum dry to obtain the final product.
[0134] The preparation method of the degradable starch-based toughening agent is as follows: 200 g corn starch and 600 mL deionized water are added to a 1000 mL reactor. 40 g glycerol is added as a plasticizer. The mixture is stirred at 95° C. for 2 hours for gelatinization. The mixture is cooled to 60° C., 20 g maleic anhydride is added, and the reaction is continued for 1 hour. The product is cooled, centrifuged, and freeze-dried to obtain the final product.
[0135] The preparation method of polyethylene glycol dimethylsiloxane copolymer is as follows: 200g α-hydrogen-ω-hydroxy-polydimethylsiloxane (molecular weight 10000g / mol) is added to a 500mL three-necked round-bottom flask. 100g methoxy polyethylene glycol (PEG molecular weight 5000Da) is added. 2g platinum catalyst (Castells catalyst) is added. The mixture is stirred and reacted for 6 hours at 100°C under nitrogen protection. The mixture is cooled to room temperature, the product is precipitated with n-hexane, filtered, and vacuum dried to obtain the final product.
[0136] The degradable double-sided leather in this embodiment further improves the softness and weather resistance of the product while maintaining excellent degradability. The polycaprolactone (PCL) film substrate not only has excellent degradability, but also provides excellent flexibility and ductility. The further increase in the content of polycaprolactone-modified polydimethylsiloxane and polylactic acid grafted polysiloxane in the silicone coating significantly improves the degradability of the coating and its compatibility with the substrate. The higher content of nano-silicon dioxide and cellulose nanocrystals not only enhances the mechanical properties of the coating, but also improves the weather resistance and chemical resistance of the product. The increased content of degradable starch-based toughening agent further improves the flexibility and folding resistance of the product. The increase in the content of hydrolyzed silk protein, triethyl citrate and nanocellulose in the surface treatment layer gives the product a more delicate touch, better skin-friendliness and stronger wear resistance.
[0137] Example 4
[0138] This embodiment provides a fourth degradable double-sided leather and a preparation method thereof. The degradable double-sided leather comprises the following components:
[0139] The surface density of the substrate is 150g / m 2 The polylactic acid (PLA) nonwoven fabric is made of 55 parts by weight of polydimethylmethylvinylsiloxane, 35 parts by weight of polycaprolactone modified polydimethylsiloxane, 25 parts by weight of polylactic acid grafted polysiloxane, 4 parts by weight of vinyltrimethoxysilane, 1.5 parts by weight of platinum catalyst, 6 parts by weight of nano-silicon dioxide, 4 parts by weight of degradable starch-based toughening agent, 0.4 parts by weight of trimethyloctadecyl ammonium chloride, 1.5 parts by weight of cellulose nanocrystals, 1.5 parts by weight of natural plant oil-based matting agent and 0.4 parts by weight of bio-based dispersant. The surface treatment layer contains 55 parts by weight of polyethylene glycol dimethylsiloxane copolymer, 12 parts by weight of hydrolyzed silk protein, 25 parts by weight of triethyl citrate and 4 parts by weight of nanocellulose.
[0140] The preparation method of the degradable double-faced leather comprises the following steps:
[0141] First, pre-treat the substrate. 2The PLA nonwoven fabric was cut into the required size, and then the surface of the substrate was activated using a plasma treatment device. The treatment parameters were: air pressure 85Pa, RF power 150W, and treatment time 90 seconds. The treated substrate was stored in a dust-free environment with a relative humidity of 55% and a temperature of 23°C.
[0142] Secondly, prepare the silica gel coating. Add 55 parts by weight of polydimethylmethylvinylsiloxane (molecular weight 35,000Da, vinyl content 1.5mol%), 35 parts by weight of polycaprolactone modified polydimethylsiloxane (PCL content 25wt%, molecular weight 32,000g / mol) and 25 parts by weight of polylactic acid grafted polysiloxane (PLA content 12wt%, molecular weight 25,000g / mol) into the reaction kettle in sequence. Stir at 450rpm for 25 minutes at 28°C. Then slowly add 6 parts by weight of nano-silicon dioxide (average particle size 40nm) and continue stirring for 50 minutes. 4 parts by weight of a degradable starch-based toughener (maleic anhydride grafting degree 12%, moisture content 3.5%), 0.4 parts by weight of trimethyl octadecyl ammonium chloride, 1.5 parts by weight of cellulose nanocrystals (length 400nm, diameter 15nm), 1.5 parts by weight of a natural vegetable oil-based matting agent (acid value 70mg KOH / g) and 0.4 parts by weight of a bio-based dispersant were added in sequence, and stirred for 13 minutes after each addition of a component. Finally, 4 parts by weight of vinyl trimethoxy silane was added and stirred for 8 minutes.
[0143] Next, the coating application is carried out. The pre-mixture is transferred to the hopper of the coater and the mixture is evenly coated on the release paper using a textured release paper as a carrier by a comma knife. The coating speed is 8m / min and the coating thickness is 27μm. The release paper coated with the mixture is passed through the preheating zone at a temperature of 67°C for 80 seconds. At the exit of the preheating zone, the pretreated substrate is covered with the semi-cured silicone layer. The substrate is pressed onto the silicone layer using a pressure roller with a roller pressure of 85N / cm. The pressed composite material is passed through the main drying zone at a temperature of 135°C for 3.5 minutes. After cooling to room temperature, the release paper is peeled off.
[0144] Then, the above coating steps are repeated to perform coating treatment on the other side of the material to obtain a double-sided coating material.
[0145] Finally, surface treatment is performed. Add 55 parts by weight of polyethylene glycol dimethylsiloxane copolymer (PEG content 35wt%, molecular weight 40,000g / mol) to the stirring kettle, stir at 300rpm, and heat to 60°C. Slowly add 12 parts by weight of hydrolyzed silk protein (molecular weight 12,000Da) and continue stirring for 30 minutes. Add 25 parts by weight of triethyl citrate and stir for 15 minutes. Finally, add 4 parts by weight of nanocellulose (diameter 8nm, length 400nm), increase the stirring speed to 500rpm, and stir for 60 minutes. Cool to room temperature and let stand for 24 hours. Use a 120-mesh treatment roller to evenly apply the surface treatment agent on both sides of the double-sided silicone coating material, with a coating weight of 17g / m 2 (per side), the coating speed is 4.5 m / min. The coated material is passed through a drying zone at a temperature of 115°C for 2.7 minutes. After cooling to room temperature, it is rolled up and stored to obtain the final degradable double-sided leather product.
[0146] In this embodiment, the preparation method of polycaprolactone modified polydimethylsiloxane is as follows: 100g of polydimethylsiloxane (molecular weight 8500g / mol) is added to a 250mL three-necked round-bottom flask. 25g of ε-caprolactone monomer and 1.2g of dibutyltin dilaurate catalyst are added. Under nitrogen protection, the temperature is raised to 145°C and stirred for reaction for 5.5 hours. Cool to room temperature, precipitate the product with ethanol, filter, and vacuum dry to obtain the final product.
[0147] The preparation method of polylactic acid grafted polysiloxane is as follows: 200g of hydroxyl-terminated polydimethylsiloxane (molecular weight 6500g / mol) is added to a 500mL three-necked round-bottom flask. 24g of L-lactic acid and 0.8g of p-toluenesulfonic acid are added as catalysts. At 145°C, the pressure is reduced to 40mbar and stirred for reaction for 7.5 hours. Cool to room temperature, precipitate the product with acetone, filter, and vacuum dry to obtain the final product.
[0148] The preparation method of the degradable starch-based toughening agent is as follows: 200 g corn starch and 600 mL deionized water are added to a 1000 mL reactor. 35 g glycerol is added as a plasticizer. The mixture is stirred at 93° C. for 1.7 hours for gelatinization. The mixture is cooled to 60° C., 17 g maleic anhydride is added, and the reaction is continued for 1 hour. The product is cooled, centrifuged, and freeze-dried to obtain the final product.
[0149] The preparation method of polyethylene glycol dimethylsiloxane copolymer is as follows: 200g α-hydrogen-ω-hydroxy-polydimethylsiloxane (molecular weight 8500g / mol) is added to a 500mL three-necked round-bottom flask. 85g methoxy polyethylene glycol (PEG molecular weight 4000Da) is added. 1.7g platinum catalyst (Castells catalyst) is added. The reaction is stirred at 95°C under nitrogen protection for 5.5 hours. The mixture is cooled to room temperature, the product is precipitated with n-hexane, filtered, and vacuum dried to obtain the final product.
[0150] The degradable double-sided leather in this embodiment achieves a comprehensive balance of performance while maintaining excellent degradability. The polylactic acid (PLA) non-woven fabric substrate has a higher surface density, providing better strength and stability while maintaining good degradability. The ratio of each component in the silicone coating has been optimized to ensure sufficient degradability while taking into account the mechanical properties and durability of the product. The content of nano-silicon dioxide and cellulose nanocrystals is moderate, which will not excessively affect the softness of the product while providing sufficient strength and wear resistance. The amount of degradable starch-based toughening agent is adjusted so that the product is not too soft while maintaining flexibility. The proportion of each component in the surface treatment layer has also been optimized to give the product a good feel, skin-friendliness and wear resistance, while maintaining excellent degradable properties.
[0151] Comparative Example 1: Degradable double-sided leather without polycaprolactone-modified polydimethylsiloxane
[0152] This comparative example is intended to verify the important role of polycaprolactone-modified polydimethylsiloxane in improving the degradability and flexibility of the product. The formula and preparation method of comparative example 1 are basically the same as those of example 1, but do not contain polycaprolactone-modified polydimethylsiloxane, as follows:
[0153] The surface density of the substrate is 50g / m 2 The silicone coating is composed of 60 parts by weight of polydimethylmethylvinylsiloxane, 10 parts by weight of polylactic acid grafted polysiloxane, 2 parts by weight of vinyltrimethoxysilane, 0.5 parts by weight of platinum catalyst, 3 parts by weight of nano-silicon dioxide, 1 part by weight of degradable starch-based toughening agent, 0.1 parts by weight of trimethyloctadecyl ammonium chloride, 0.5 parts by weight of cellulose nanocrystals, 0.5 parts by weight of natural plant oil-based matting agent and 0.1 parts by weight of bio-based dispersant. The composition of the surface treatment layer is the same as that of Example 1.
[0154] The preparation method is basically the same as that of Example 1, but when preparing the silicone coating, the polycaprolactone-modified polydimethylsiloxane is not added, and the amount of polydimethylmethylvinylsiloxane is increased accordingly.
[0155] Through comparative tests, it was found that although the double-faced leather prepared in Comparative Example 1 had certain degradability, its degradation rate was significantly lower than that of Example 1. In addition, the flexibility and folding resistance of the product were not as good as those of Example 1. This shows that polycaprolactone-modified polydimethylsiloxane plays a key role in improving the degradability and flexibility of the product. Its mechanism of action may be that the polycaprolactone segment increases the hydrophilicity and hydrolyzability of the silica gel network, while providing more flexible segments, thereby improving the overall performance of the product.
[0156] Comparative Example 2: Degradable double-faced leather without polylactic acid grafted polysiloxane
[0157] This comparative example is intended to verify the importance of polylactic acid grafted polysiloxane in enhancing product degradability and improving compatibility between coating and substrate. The formula and preparation method of comparative example 2 are basically the same as those of example 2, but do not contain polylactic acid grafted polysiloxane, as follows:
[0158] The surface density of the substrate is 120g / m 2 The polyhydroxybutyric acid-hydroxyvaleric acid copolymer (PHBV) fiber cloth. The silica gel coating is composed of 70 parts by weight of polydimethylmethylvinylsiloxane, 30 parts by weight of polycaprolactone modified polydimethylsiloxane, 3.5 parts by weight of vinyltrimethoxysilane, 1.25 parts by weight of platinum catalyst, 5.5 parts by weight of nano silicon dioxide, 3 parts by weight of degradable starch-based toughening agent, 0.3 parts by weight of trimethyloctadecyl ammonium chloride, 1.25 parts by weight of cellulose nanocrystals, 1.25 parts by weight of natural vegetable oil-based matting agent and 0.3 parts by weight of bio-based dispersant. The composition of the surface treatment layer is the same as that of Example 2.
[0159] The preparation method is basically the same as that of Example 2, but when preparing the silica gel coating, no polylactic acid grafted polysiloxane is added, and the amount of polydimethylmethylvinylsiloxane is increased accordingly.
[0160] Through comparative tests, it was found that the double-faced leather prepared in Comparative Example 2 was slightly inferior to that in Example 2 in terms of degradability, and the bonding strength between the coating and the substrate was significantly reduced. This shows that polylactic acid grafted polysiloxane plays an important role in enhancing the degradability of the product and improving the compatibility between the coating and the substrate. Its mechanism of action may be that the polylactic acid segment increases the hydrophilicity and hydrolyzability of the silica gel network, and at the same time, through the interaction of forming hydrogen bonds with the polyester structure in the substrate, the bonding strength between the coating and the substrate is improved.
[0161] Comparative Example 3: Degradable double-faced leather without degradable starch-based toughening agent
[0162] This comparative example is intended to verify the importance of degradable starch-based toughening agents in improving product flexibility and folding resistance. The formula and preparation method of comparative example 3 are basically the same as those of example 3, but do not contain degradable starch-based toughening agents, as follows:
[0163] The substrate is a polycaprolactone (PCL) film with a thickness of 50 μm. The silica gel coating is composed of 65 parts by weight of polydimethylmethylvinylsiloxane, 40 parts by weight of polycaprolactone-modified polydimethylsiloxane, 30 parts by weight of polylactic acid grafted polysiloxane, 5 parts by weight of vinyltrimethoxysilane, 2 parts by weight of platinum catalyst, 8 parts by weight of nano-silicon dioxide, 0.5 parts by weight of trimethyloctadecylammonium chloride, 2 parts by weight of cellulose nanocrystals, 2 parts by weight of natural plant oil-based matting agent and 0.5 parts by weight of bio-based dispersant. The composition of the surface treatment layer is the same as that of Example 3.
[0164] The preparation method is basically the same as that of Example 3, but when preparing the silicone coating, no degradable starch-based toughening agent is added, and the amount of polydimethylmethylvinylsiloxane is increased accordingly.
[0165] Through comparative tests, it was found that although the double-faced leather prepared in Comparative Example 3 maintained good degradability, its flexibility and folding resistance were significantly lower than those in Example 3. This shows that the degradable starch-based toughening agent plays a key role in improving the flexibility and folding resistance of the product. Its mechanism of action may be that the starch-based toughening agent forms flexible micro-regions in the silica gel network, and at the same time, through hydrogen bonding with other components, it enhances the cohesion of the material, thereby improving the flexibility and folding resistance of the product.
[0166] Comparative Example 4: Degradable double-sided leather without nano-silicon dioxide
[0167] This comparative example is intended to verify the importance of nano-silicon dioxide in improving the mechanical strength and wear resistance of the product. The formula and preparation method of comparative example 4 are basically the same as those of example 4, but do not contain nano-silicon dioxide, as follows:
[0168] The surface density of the substrate is 150g / m 2 The polylactic acid (PLA) nonwoven fabric is prepared from polydimethyl methylvinylsiloxane (PDMS), polycaprolactone modified polydimethylsiloxane (PDMS), polylactic acid grafted polysiloxane (PLA) (PDMS), vinyl trimethoxysilane (VMS), platinum catalyst (PTM), degradable starch-based toughening agent (PDMS), trimethyl octadecyl ammonium chloride (CTAC), cellulose nanocrystals (CNC), natural vegetable oil-based matting agent (PDM), and bio-based dispersant (BDP). The composition of the surface treatment layer is the same as that of Example 4.
[0169] The preparation method is basically the same as that of Example 4, but when preparing the silica gel coating, no nano-silicon dioxide is added, and the amount of polydimethylmethylvinylsiloxane is increased accordingly.
[0170] Through comparative tests, it was found that the double-faced leather prepared in Comparative Example 4 was similar to that in Example 4 in terms of degradability, but its mechanical strength and wear resistance were significantly reduced. This shows that nano-silicon dioxide plays an important role in improving the mechanical strength and wear resistance of the product. Its mechanism of action may be that nano-silicon dioxide forms chemical bonds and physical entanglements with the siloxane network, thereby enhancing the overall structure of the material, while its high specific surface area provides more friction and energy dissipation interfaces, thereby improving the mechanical strength and wear resistance of the product.
[0171] Comparative Example 5: Degradable double-sided leather without hydrolyzed silk protein
[0172] This comparative example is intended to verify the importance of hydrolyzed silk protein in improving the feel and skin-friendliness of the product. The formula and preparation method of comparative example 5 are basically the same as those of example 1, but the surface treatment layer does not contain hydrolyzed silk protein, as follows:
[0173] The composition of the substrate and the silicone coating is the same as that of Example 1. The surface treatment layer comprises 45 parts by weight of polyethylene glycol dimethylsiloxane copolymer, 10 parts by weight of triethyl citrate and 1 part by weight of nanocellulose.
[0174] The preparation method is basically the same as that of Example 1, but when preparing the surface treatment layer, no hydrolyzed silk protein is added, and the amount of polyethylene glycol dimethylsiloxane copolymer is increased accordingly.
[0175] Through comparative tests, it was found that the double-faced leather prepared in Comparative Example 5 was similar to that in Example 1 in terms of degradability and mechanical properties, but its hand feel and skin affinity were significantly reduced. This shows that hydrolyzed silk protein plays a key role in improving the hand feel and skin affinity of the product. Its mechanism of action may be that the rich amino acid composition of hydrolyzed silk protein provides good moisture retention and skin affinity, while its special secondary structure helps to form a soft surface layer, thereby improving the overall touch and comfort of the product.
[0176] Comparative Example 6: Degradable double-faced leather without triethyl citrate
[0177] This comparative example is intended to verify the importance of triethyl citrate in improving the softness and weather resistance of the product. The formula and preparation method of comparative example 6 are basically the same as those of example 2, but the surface treatment layer does not contain triethyl citrate, as follows:
[0178] The composition of the substrate and the silicone coating is the same as that of Example 2. The surface treatment layer comprises 70 parts by weight of polyethylene glycol dimethylsiloxane copolymer, 10 parts by weight of hydrolyzed silk protein and 3 parts by weight of nanocellulose.
[0179] The preparation method is basically the same as that of Example 2, but when preparing the surface treatment layer, triethyl citrate is not added, and the amount of polyethylene glycol dimethylsiloxane copolymer is increased accordingly.
[0180] Through comparative tests, it was found that the double-faced leather prepared in Comparative Example 6 was similar to that in Example 2 in terms of degradability, but its softness and weather resistance were significantly reduced. This shows that triethyl citrate plays an important role in improving the softness and weather resistance of the product. Its mechanism of action may be that triethyl citrate, as an efficient plasticizer, can reduce the interaction between polymer segments and increase the freedom of movement of molecular chains, thereby improving the softness of the material. At the same time, its special chemical structure also helps to absorb ultraviolet rays and improve the weather resistance of the product.
[0181] Through these six comparative examples, we can clearly see the importance of each key component in the present invention and its synergistic effect. The combination of polycaprolactone modified polydimethylsiloxane and polylactic acid grafted polysiloxane not only improves the degradability of the product, but also improves the compatibility between the coating and the substrate. The addition of degradable starch-based toughening agent and nano-silicon dioxide respectively improves the flexibility and mechanical strength of the product. The combination of hydrolyzed silk protein and triethyl citrate optimizes the surface properties of the product and improves the feel and weather resistance. The synergistic effect of these components enables the degradable double-sided leather of the present invention to have excellent mechanical properties, comfortable touch and good durability while maintaining excellent degradability, which is significantly superior to the prior art and reflects the creativity and superiority of the present invention.
[0182] The present invention also designs a series of professional testing experiments, which will cover aspects such as the material's degradability, mechanical properties, comfort and environmental friendliness, so as to fully demonstrate the innovations and advantages of the present invention.
[0183] Test plan design:
[0184] 1. Degradability test
[0185] Composting degradation test was conducted according to ISO 14855 standard. The samples were cut into 5cm×5cm pieces and buried in standard compost. The samples were degraded at 58±2℃ and relative humidity>90%. The weight loss and CO2 release were measured every 30 days, and the test period was 180 days.
[0186] 2. Mechanical properties test
[0187] a) Tensile strength and elongation at break: According to GB / T 1040.3-2006 standard, use a universal material testing machine for testing, with a tensile speed of 50 mm / min.
[0188] b) Tear strength: tested in accordance with GB / T 16578.1-2008 standard using a universal material testing machine.
[0189] c) Folding resistance: According to GB / T 3903.2-2008 standard, the test was carried out using an MIT folding tester with a load of 500g.
[0190] 3. Comfort test
[0191] a) Air permeability: According to GB / T 5453-1997 standard, use an air permeability tester to test.
[0192] b) Hygroscopicity: According to GB / T 21655.1-2008 standard, the moisture absorption rate is tested at relative humidity of 65% and 90%.
[0193] c) Hand feel evaluation: Invite 10 professional judges to conduct a blind test and score on a scale of 1-5 (1 is the worst and 5 is the best).
[0194] 4. Environmental friendliness test
[0195] a) Heavy metal content: According to GB / T 28001-2011 standard, ICP-MS is used to determine the content of heavy metals such as lead, cadmium, mercury and chromium.
[0196] b) Volatile organic compound (VOC) emission: VOC emission was measured using gas chromatography-mass spectrometry in accordance with GB / T 29784-2013.
[0197] 5. Weather resistance test
[0198] According to GB / T 16422.2-2014 standard, the xenon arc lamp aging test chamber was used for testing, with a cumulative irradiation of 1000 hours. The color difference and mechanical property changes of the samples were compared before and after the test.
[0199] The test results are as follows:
[0200] Table 1. Degradability test results (after 180 days)
[0201] sample Weight loss rate (%) <![CDATA[CO2 evolution rate (mg / g)]]> Example 1 92.5 680 Example 2 94.8 695 Example 3 96.2 710 Example 4 95.5 705 Comparative Example 1 78.3 575 Comparative Example 2 82.1 605 Comparative Example 3 91.8 675 Comparative Example 4 93.7 690 Comparative Example 5 94.2 695 Comparative Example 6 94.5 700
[0202] Table 2. Mechanical properties test results
[0203] sample Tensile strength(MPa) Elongation at break (%) Tear strength(N / mm) Folding resistance (times) Example 1 18.5 280 45 100000 Example 2 22.3 310 52 120000 Example 3 20.7 295 48 110000 Example 4 21.5 305 50 115000 Comparative Example 1 15.8 240 38 80000 Comparative Example 2 17.2 255 41 85000 Comparative Example 3 19.8 270 44 90000 Comparative Example 4 16.5 285 40 95000 Comparative Example 5 20.2 290 47 105000 Comparative Example 6 19.5 285 46 100000
[0204] Table 3. Comfort and environmental friendliness test results
[0205]
[0206] Table 4. Weathering test results (after 1000 hours)
[0207]
[0208]
[0209] According to the test results, Example 4 exhibits the best comprehensive performance and can be regarded as the best embodiment of the present invention.
[0210] The analysis and discussion are as follows:
[0211] 1. Degradability: All examples of the present invention exhibit excellent degradability, with the weight loss rate and CO2 release after 180 days being higher than those of the comparative examples. This is mainly due to the synergistic effect of polycaprolactone-modified polydimethylsiloxane and polylactic acid-grafted polysiloxane. These two modified siloxanes introduce easily degradable ester bonds while maintaining the excellent properties of silica gel, significantly improving the biodegradability of the material.
[0212] 2. Mechanical properties: The examples of the present invention are superior to the comparative examples in terms of tensile strength, elongation at break, tear strength and folding resistance. Such excellent mechanical properties are derived from the synergistic reinforcement effect of nano-silicon dioxide, cellulose nano-crystals and degradable starch-based toughening agents. Nano-silicon dioxide provides a good reinforcement effect, cellulose nano-crystals increase the toughness of the material, and the degradable starch-based toughening agent improves the flexibility and folding resistance of the material.
[0213] 3. Comfortability: The embodiments of the present invention excel in air permeability, hygroscopicity and hand feel. This is mainly due to the addition of hydrolyzed silk protein and triethyl citrate. Hydrolyzed silk protein provides excellent hygroscopicity and skin affinity, while triethyl citrate increases the softness of the material. The synergistic effect of these two ingredients makes the product of the present invention have excellent comfort.
[0214] 4. Environmental friendliness: The examples of the present invention show lower heavy metal content and VOC emission, which indicates that the product has good environmental friendliness. This may be due to the fact that the present invention uses a variety of bio-based materials and environmentally friendly additives, reducing the use of harmful substances.
[0215] 5. Weatherability: The examples of the present invention performed well in the weatherability test, with small color difference and high mechanical property retention. This may be due to the addition of triethyl citrate, which not only improves the flexibility of the material as a plasticizer, but also may play the role of a UV absorber, improving the material's anti-aging ability.
[0216] Unexpected technical effects:
[0217] 1. Unexpected balance between degradability and mechanical properties: The present invention successfully achieves a perfect combination of high degradability and excellent mechanical properties, which is difficult to achieve in traditional degradable materials. This balance is mainly due to the synergistic effect of modified siloxane, nanofiller and bio-based toughening agent.
[0218] 2. Excellent comfort: The product of the present invention exhibits far more comfort than expected, especially in terms of air permeability and hygroscopicity. This may be due to the formation of microscopic channels in the silica gel network by hydrolyzed silk protein, which greatly improves the air permeability and hygroscopicity of the material.
[0219] 3. Excellent weather resistance: The product of the present invention exhibits unexpectedly strong weather resistance, which is extremely rare in degradable materials. This may be because triethyl citrate not only plays a plasticizing role, but also forms a protective film on the surface of the material, effectively blocking UV radiation and oxygen erosion.
[0220] 4. Synergistic degradation mechanism: The test results show that the product of the present invention not only degrades quickly, but also has a more uniform and complete degradation process. This may be due to the fact that different degradable components (such as polycaprolactone, polylactic acid, starch) promote each other during the degradation process, forming a synergistic degradation mechanism.
[0221] 5. Low VOC emission: The product of the present invention exhibits VOC emission far lower than expected, which is very rare for composite materials containing multiple organic components. This may be due to the complex network structure formed by hydrolyzed silk protein and nanofillers, which effectively encapsulates other organic components and greatly reduces VOC emission.
[0222] In summary, the present invention has successfully developed a double-face leather material with high degradability, excellent mechanical properties, excellent comfort and outstanding environmental friendliness through the exquisite proportion of multiple innovative components and unique preparation process. This material has broad application prospects in the context of sustainable development and circular economy, and is expected to bring about revolutionary changes in many fields such as clothing, luggage, and furniture.
[0223] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A degradable double-face leather, characterized in that: Includes the following components: (1) Substrate, selected from one or more of the following: a) Surface density is 50-150g / m 2 Polylactic acid PLA non-woven fabric; b) Surface density is 60-180g / m 2 PHBV fiber cloth; c) a polycaprolactone PCL film having a thickness of 20-80 μm; (2) Silicone coating, including: a) 40-60 parts by weight of polydimethylmethylvinylsiloxane; b) 20-40 parts by weight of polycaprolactone modified polydimethylsiloxane; c) 10-30 parts by weight of polylactic acid grafted polysiloxane; d) 2-5 parts by weight of vinyltrimethoxysilane; e) 0.5-2 parts by weight of a platinum catalyst; f) 3-8 parts by weight of nano silicon dioxide; g) 1-5 parts by weight of a degradable starch-based toughening agent; h) 0.1-0.5 parts by weight of trimethyloctadecylammonium chloride; i) 0.5-2 parts by weight of cellulose nanocrystals; j) 0.5-2 parts by weight of a natural vegetable oil-based matting agent; k) 0.1-0.5 parts by weight of a bio-based dispersant; (3) Surface treatment layer, including: a) 40-60 parts by weight of polyethylene glycol dimethyl siloxane copolymer; b) 5-15 parts by weight of hydrolyzed silk protein; c) 10-30 parts by weight of triethyl citrate; d) 1-5 parts by weight of nanocellulose.
2. The degradable double-face leather according to claim 1, characterized in that: The PCL content of the polycaprolactone-modified polydimethylsiloxane is 10-30 wt % and the molecular weight is 15,000-40,000 g / mol.
3. The degradable double-face leather according to claim 1, characterized in that: The PLA content of the polylactic acid grafted polysiloxane is 5-15 wt % and the molecular weight is 10,000-30,000 g / mol.
4. The degradable double-face leather according to claim 1, characterized in that: The maleic anhydride grafting degree of the degradable starch-based toughening agent is 5-15%, and the water content is ≤5%.
5. The degradable double-face leather according to claim 1, characterized in that: The polyethylene glycol dimethylsiloxane copolymer has a PEG content of 20-40 wt % and a molecular weight of 15,000-50,000 g / mol.
6. A method for preparing the degradable double-face leather according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Substrate pretreatment: a) cutting the selected degradable substrate into required sizes; b) using a plasma treatment device to activate the surface of the substrate, wherein the gas pressure is 50-100 Pa, the radio frequency power is 50-200 W, and the treatment time is 30-120 seconds; c) storing the treated substrate in a dust-free environment with a relative humidity of 40-60% and a temperature of 20-25° C.; (2) Preparation of silicone coating: a) adding polydimethylmethylvinylsiloxane, polycaprolactone-modified polydimethylsiloxane and polylactic acid-grafted polysiloxane in a reaction kettle in order according to the formula ratio, and stirring at 25-30° C. at a speed of 300-500 rpm for 15-30 minutes; b) Slowly add nano-silicon dioxide and continue stirring for 30-60 minutes; c) adding a degradable starch-based toughening agent, trimethyl octadecyl ammonium chloride, cellulose nanocrystals, a natural vegetable oil-based matting agent, and a bio-based dispersant in sequence, stirring for 10-15 minutes after each addition of a component; d) finally adding vinyltrimethoxysilane and stirring for 5-10 minutes; (3) Coating application: a) transferring the premix into the hopper of the coater; b) using a release paper with a texture as a carrier, the mixture is evenly coated on the release paper by a comma knife, the coating speed is 5-10 m / min, and the coating thickness is 20-30 μm; c) passing the release paper coated with the mixture through a preheating zone at a temperature of 60-70° C. for 60-90 seconds; d) at the exit of the preheating zone, covering the pretreated substrate on the semi-cured silicone layer; e) Using a pressure roller to press the substrate onto the silicone layer, the roller pressure is 50-100 N / cm; f) passing the laminated composite material through a main drying zone at a temperature of 120-140° C. for 2-4 minutes; g) cooling to room temperature, and then peeling off the release paper; (4) Double-sided coating: Repeat steps (2) and (3) to coat the other side of the material; (5) Surface treatment: a) adding polyethylene glycol dimethylsiloxane copolymer into a stirred tank, stirring at 300 rpm, and heating to 60° C.; b) slowly adding hydrolyzed silk protein and continuing stirring for 30 minutes; c) adding triethyl citrate and stirring for 15 minutes; d) finally adding nanocellulose, increasing the stirring speed to 500 rpm, and stirring for 60 minutes; e) Cool to room temperature and let stand for 24 hours; f) Use a 120 mesh treatment roller to evenly apply the surface treatment agent on both sides of the double-sided silicone coating material, with a coating weight of 10-20g / m 2 (per side), coating speed is 3-5m / min; g) passing the coated material through a drying zone at a temperature of 100-120°C for 2-3 minutes; h) Cool to room temperature and roll up for storage.
7. The method according to claim 6, characterized in that The preparation method of the polycaprolactone modified polydimethylsiloxane comprises: a) Add 100 g of polydimethylsiloxane (molecular weight 5000-10000 g / mol) into a three-necked round-bottom flask; b) adding 10-30 g of ε-caprolactone monomer and 0.5-1.5 g of stannate catalyst; c) Under nitrogen protection, heat to 130-150°C and stir to react for 4-6 hours; d) Cool to room temperature, precipitate the product with ethanol, filter, and vacuum dry to obtain the final product.
8. The method according to claim 6, characterized in that The preparation method of the polylactic acid grafted polysiloxane comprises: a) adding 200 g of hydroxyl-terminated polydimethylsiloxane (molecular weight 3000-8000 g / mol) into a three-necked round-bottom flask; b) adding 10-30 g L-lactic acid and 0.5-1.0 g p-toluenesulfonic acid as catalysts; c) at 130-150° C., reducing the pressure to 20-50 mbar, stirring and reacting for 6-8 hours; d) Cool to room temperature, precipitate the product with acetone, filter, and vacuum dry to obtain the final product.
9. The method according to claim 6, characterized in that The preparation method of the degradable starch-based toughening agent comprises: a) Add 200 g corn starch and 600 mL deionized water into a reactor; b) adding 20-40 g of glycerol as a plasticizer; c) stirring at 90-95° C. for 1-2 hours for gelatinization; d) Cool to 60°C, add 10-20g of maleic anhydride, and continue the reaction for 1 hour; e) cooling the product, centrifuging and freeze-drying to obtain the final product.
10. The method according to claim 6, characterized in that The preparation method of the polyethylene glycol dimethylsiloxane copolymer comprises: a) adding 200 g of α-hydrogen-ω-hydroxy-polydimethylsiloxane (molecular weight 5000-10000 g / mol) into a three-necked round-bottom flask; b) adding 50-100 g of methoxy polyethylene glycol (PEG molecular weight 1000-5000 Da); c) adding 1-2 g of platinum catalyst; d) stirring and reacting at 80-100° C. under nitrogen protection for 4-6 hours; e) cooling to room temperature, precipitating the product with n-hexane, filtering, and vacuum drying to obtain the final product.